Evaluation of Bone Marrow Texture and Trabecular Changes With Quantitative DCE-MRI and QCT in Alloxan-Induced Diabetic Rabbit Models - Chen, Pianpian; Zha, Yunfei; Wang, Li; Li, Liang; Hu, Lei; Xing, Dong; Liu, Baiyu; Yang, Liu; Yang, Qi; Liu, Changsheng; Liu, Huan; Liu, Weiyin (Frontiers in Endocrinology, 2021)
Purpose: To investigate whether the microvascular permeability of lumbar marrow and bone trabecular changes in early-stage diabetic rabbits can be quantitatively evaluated using dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI), quantitative computed tomography, and texture-analyzed permeability parameter Ktrans map of DCE-MRI. Materials and Methods This prospective study included 24 rabbits randomly assigned to diabetic (n=14) and control (n=10) groups. All rabbits underwent sagittal MRI of the lumbar region at 0, 4, 8, 12, and 16 weeks after alloxan injection. Pearson correlation coefficient was performed to determine the correlation between permeability parameter and bone mineral density (BMD). Repeated measures ANOVA was used to analyze the changes in lumbar BMD over time in each group and the texture parameters of diabetic rabbit lumbar marrow at different time points. Mann-Whitney U rank sum test was used to compare the differences of each index between the two groups and calculate the area under the curve (AUC). Results BMD was correlated with Ktrans, Kep, and Ve, but not with Vp. At weeks 0-16, the BMD of the rabbits in the diabetic and normal groups was not statistically significant, but the change in BMD showed an overall downward trend. For texture analysis, entropy, energy, and Uniformized positive pixel（UPP） parameters extracted from the Ktrans map showed significant differences from week 0 to 16 between the two groups. The identification ability at 8-12 weeks was higher than that at 12-16 weeks, and the AUCs were 0.734, 0.766, and 0.734, respectively (P, .05 for all). Conclusions The changes in bone mineral density measured using quantitative computed tomography occurred later than those measured using bone trabecular morphometry. Texture analysis parameters based on dynamic contrast-enhanced magnetic resonance imaging quantitative parameter Ktrans map are feasible to identify early changes in lumbar marrow structure in diabetic rabbits.